Auto(trans)formação com professoras e (re)organização curricular: desdobramentos e desafios da pedagogia da educação popular na escola pública - Signor, Patrícia (2021)
This thesis is part of the Formation Research Line, Knowledge and Professional Development of the Graduate Program in Education at the Federal University of Santa Maria / RS. The investigation proposed to study and understand the curricular (re)organizations throughout the proposal construction of a public school that approaches the popular education pedagogy, making the Dialogic Circles Investigative-self(trans)formative as a procedural construction for the self(trans)formation with teachers and strengthening the popular education possibilities in public schools. During writing, it was necessary to understand the self(trans)formation processes with teachers and the curricular (re)organizations of a public school basic education, which proposes to work with the popular education pedagogy. To carry out the research, the permanent formation concepts (FREIRE, 2011a), teacher formation (IMBERNÓN, 2010, 2011) were intertwined, together with permanent self(trans)formation (HENZ, 2014; 2015). The work brings the contributions of Freire's popular education pedagogy (2014; 2013; 2011); the curriculum conception presented in the text is based on Sacristán (2013), Silva (2014), Arroyo (2013) and Moreira e Silva (1995). The methodological approach chosen was the qualitative one, based on Ghedin & Franco (2011); André (2001); Duarte (2002); Michel (2009), based on the Dialogic Circles Investigative-self(trans)formation (HENZ, 2014), (FREITAS, 2015), (HENZ; FREITAS, 2015) (HENZ; TONIOLO, 2015 and 2017) that privilege spaces for dialogue in teachers’ self (trans)formation. The methodology is characterized by formation research (JOSSO, 2004, 2010) with case study traces of (YIN, 2005), as it privileges a specific context and seeks to investigate particularities intensively. The research carried out ten Dialogic Circles Investigative-self(trans)formation with the educators collective from the State School of Basic Education in Barra Funda (RS), in order to study the possibilities and challenges of curricular (re)organization under the perspective of popular education pedagogy in public schools, with a view to the possibility of renewing and valuing public schools as a place to learn, to grow, to politicize, to humanize and to be happy. The Dialogic Circles Investigative-self(trans)formation interpretation was in the light of hermeneutics (GADAMER, 1998; FLICKINGER, 2014, KRONBAUER, 2014) with dialogue as a contribution to the moments of self(trans)formation of educators, co-authors of the research , based on every day and disturbing themes that emerged from the Circles. The leading researcher interventions at the school provided moments conducive to the awareness that self(trans)formation, going through historical moments in the school's trajectory, such as the COVID-19 pandemic, strikes and socio-anthropological research elaboration, contributing with unprecedented viability in a more problematic construction, dialogical and human education.